Laparoscopic Liver Resection: Surgical Techniques - Sullivan, Brittany G.; Wolf, Ronald; Jutric, Zeljka (Digestive Disease Interventions, 2022)
Laparoscopic liver resection has evolved from a technique to remove small anterior liver lesions with smaller incisions to a major method for the performance of almost every type of liver resection.
Keywords: liver resection; minimally invasive; robotic; laparoscopic